2018
DOI: 10.3390/agronomy8120299
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination in Relation to Total Sugar and Starch in Endosperm Mutant of Sweet Corn Genotypes

Abstract: The use of combinations of two or more genes controlling carbohydrate characters of corn is an attractive way to improve table quality of sweet corn. Poor seed quality of the inbred lines hinders the progress of this strategy for hybrid seed production. The objective of this study was to evaluate sweet corn inbred lines with combinations of double and triple recessive genes for germination percentage, seed vigor, total sugar content, and starch content. Eleven sweet corn genotypes including seven inbred lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
3
12
1
2
Order By: Relevance
“…However, early mature genotypes can have higher yield than late mature genotypes in some cases. In maize, early mature hybrids with higher seedling strength had higher grain yield than late mature genotypes with poor seed vigor [62], and the genotypes with early maturity and resistance to late season drought had higher grain yield than late maturing genotypes [63].…”
Section: Correlationmentioning
confidence: 99%
“…However, early mature genotypes can have higher yield than late mature genotypes in some cases. In maize, early mature hybrids with higher seedling strength had higher grain yield than late mature genotypes with poor seed vigor [62], and the genotypes with early maturity and resistance to late season drought had higher grain yield than late maturing genotypes [63].…”
Section: Correlationmentioning
confidence: 99%
“…Conceituado como o conjunto de atributos que confere à semente a capacidade para germinar, emergir e resultar rapidamente em plântulas normais, o vigor influencia, geralmente, no estabelecimento de uma população de plantas adequada sobre variações de condições ambientais (Marcos Filho, 2017). Contudo, para cultura do milho doce, estudos revelam um efeito prejudicial do açúcar na germinação de suas sementes, afetando a emergência à campo, a qual não apresenta correlação positiva com o teor de açúcar em sementes secas (Pairochteerakul, 2018).…”
Section: Substratosunclassified
“…However, the adverse effects on seed qualities were found in sweet corn genotypes with two or more recessive genes controlling sugar synthesis. Pairochteerakul et al [11] reported that incorporations of either bt 2 or sh 2 gene into wx background resulted in low germination percentage and poor seedling vigor. is situation would be unfavorable for hybrid seed production.…”
Section: Introductionmentioning
confidence: 99%